Overview of HVCMOS pixel sensors - Peric, Ivan; Eber, R.; Ehrler, F.; Augustin, Heiko; Berger, N.; Dittmeier, Sebastian; Graf, Christian; Huth, Lennart; Perrevoort, Ann-Kathrin; Phillipp, R.; Repenning, Jan; Bruch, Dorothea vom; et al. (Journal of Instrumentation, 2015)
High voltage CMOS (HVCMOS) sensors are presently considered for the use in Mu3e experiment, ATLAS and CLIC. These sensors can be implemented in commercial HVCMOS processes. HVCMOS sensors feature fast charge collection by drift and high radiation tolerance. The sensor element is an n-well/p-type diode. This proceeding-paper gives an overview of HVCMOS projects and the recent results.
Gesehen am 02.07.2020